Asymmetric α-amination of 3-substituted oxindoles using chiral bifunctional phosphine catalysts - Jin, Qiao-Wen; Chai, Zhuo; Huang, You-Ming; Zou, Gang; Zhao, Gang (Beilstein Journal of Organic Chemistry, 2016)
A highly enantioselective α-amination of 3-substituted oxindoles with azodicarboxylates catalyzed by amino acids-derived chiral phosphine catalysts is reported. The corresponding products containing a tetrasubstituted carbon center attached to a nitrogen atom at the C-3 position of the oxindole were obtained in high yields and with up to 98% ee.
Keywords: 3-aminooxindoles; asymmetric catalysis; phosphine catalyst; tetrasubstituted stereogenic carbon centers

(untitled) - Dounay, A. B.; Overman, L. E. (Chem. Rev., 2003)

(untitled) - Heimgartner, H. (Angew. Chem., 1991)
Angew. Chem., Int. Ed. Engl. 1991, 30, 238–264. doi:10.1002/anie.199102381

(untitled) - Arend, M. (Angew. Chem., 1999)
Angew. Chem., Int. Ed. 1999, 38, 2873–2874. doi:10.1002/(SICI)1521-3773(19991004)38:19<2873::AID-ANIE2873>3.0.CO;2-P

(untitled) - Bergmeier, S. C. (Tetrahedron, 2000)

(untitled) - Ooi, T.; Takahashi, M.; Doda, K.; Maruoka, K. (J. Am. Chem. Soc., 2002)

(untitled) - Suri, J. T.; Steiner, D. D.; Barbas, C. F., III (Org. Lett., 2005)

(untitled) - Poulsen, T. B.; Alemparte, C.; Jorgensen, K. A. (J. Am. Chem. Soc., 2005)

(untitled) - Cheng, L.; Liu, L.; Wang, D.; Chen, Y.-J. (Org. Lett., 2009)

(untitled) - Qian, Z.-Q.; Zhou, F.; Du, T.-P.; Wang, B.-L.; Ding, M.; Zhao, X.-L.; Zhou, J. (Chem. Commun., 2009)

(untitled) - Zhou, F.; Ding, M.; Liu, Y.-L.; Wang, C.-H.; Ji, C.-B.; Zhang, Y.-Y.; Zhou, J. (Adv. Synth. Catal., 2011)

(untitled) - Bui, T.; Borregan, M.; Barbas, C. F., III (J. Org. Chem., 2009)

(untitled) - Bui, T.; Hernández-Torres, G.; Milite, C.; Barbas, C. F., III (Org. Lett., 2010)

(untitled) - Mouri, S.; Chen, Z.; Mitsunuma, H.; Furutachi, M.; Matsunaga, S.; Shibasaki, M. (J. Am. Chem. Soc., 2010)

(untitled) - Yang, Z.; Wang, Z.; Bai, S.; Shen, K.; Chen, D.; Liu, X.; Lin, L.; Feng, X. (Chem. – Eur. J., 2010)

(untitled) - Wang, S.-X.; Han, X.; Zhong, F.; Wang, Y.; Lu, Y. (Synlett, 2011)

(untitled) - Zhao, Q.-Y.; Lian, Z.; Wei, Y.; Shi, M. (Chem. Commun., 2012)

(untitled) - Fan, Y. C.; Kwon, O. (Chem. Commun., 2013)

(untitled) - Wei, Y.; Shi, M. (Chem. – Asian J., 2014)

(untitled) - Declerck, V.; Martinez, J.; Lamaty, F. (Chem. Rev., 2009)

(untitled) - Basavaiah, D.; Reddy, B. S.; Badsara, S. S. (Chem. Rev., 2010)

(untitled) - Wei, Y.; Shi, M. (Chem. Rev., 2013)

U.S. Patent - Rauhut, M.; Currier, H. (Preparation of Dialkyl 2-Methylene Glutarates, 1963)

(untitled) - McClure, J. D. (J. Org. Chem., 1970)

(untitled) - Zhao, Q.-Y.; Pei, C.-K.; Guan, X.-Y.; Shi, M. (Adv. Synth. Catal., 2011)

(untitled) - Zhang, X.-N.; Shi, M. (Eur. J. Org. Chem., 2012)

(untitled) - Shi, Z.; Yu, P.; Loh, T.-P.; Zhong, G. (Angew. Chem., 2012)
Angew. Chem., Int. Ed. 2012, 51, 7825–7829. doi:10.1002/anie.201203316

(untitled) - Takizawa, S.; Nguyen, T. M.-N.; Grossmann, A.; Enders, D.; Sasai, A. (Angew. Chem., 2012)
Angew. Chem., Int. Ed. 2012, 51, 5423–5426. doi:10.1002/anie.201201542

(untitled) - White, D. A.; Baizer, M. M. (Tetrahedron Lett., 1973)

(untitled) - Trost, B. M.; Li, C.-J. (J. Am. Chem. Soc., 1994)

(untitled) - Trost, B. M.; Dake, G. R. (J. Org. Chem., 1997)

(untitled) - Chung, Y. K.; Fu, G. C. (Angew. Chem., 2009)
Angew. Chem., Int. Ed. 2009, 48, 2225–2227. doi:10.1002/anie.200805377

(untitled) - Smith, S. W.; Fu, G. C. (J. Am. Chem. Soc., 2009)

(untitled) - Sun, J.; Fu, G. C. (J. Am. Chem. Soc., 2010)

(untitled) - Lundgren, R. J.; Wilsily, A.; Marion, N.; Ma, C.; Chung, Y. K.; Fu, G. C. (Angew. Chem., 2013)
Angew. Chem. Int. Ed. 2013, 52, 2525–2528. doi:10.1002/anie.201208957

(untitled) - Wang, T.; Yao, W.; Zhong, F.; Pang, G. H.; Lu, Y. (Angew. Chem., 2014)
Angew. Chem., Int. Ed. 2014, 53, 2964–2968. doi:10.1002/anie.201307757

(untitled) - Mindal, M.; Ibrahim, A. A.; Wheeler, K. A.; Kerrigan, N. J. (Org. Lett., 2010)

(untitled) - Xiao, H.; Chai, Z.; Zheng, C.-W.; Yang, Y.-Q.; Liu, W.; Zhang, J.-K.; Zhao, G. (Angew. Chem., 2010)
Angew. Chem., Int. Ed. 2010, 49, 4467–4470. doi:10.1002/anie.201000446

(untitled) - Han, X.; Wang, Y.; Zhong, F.; Lu, Y. (J. Am. Chem. Soc., 2011)

(untitled) - Xiao, H.; Chai, Z.; Cao, D.; Wang, H.; Chen, J.; Zhao, G. (Org. Biomol. Chem., 2012)

(untitled) - Chai, Z.; Zhao, G. (Catal. Sci. Technol., 2012)

(untitled) - Cao, D.; Chai, Z.; Zhang, J.; Ye, Z.; Xiao, H.; Wang, H.; Chen, J.; Wu, X.; Zhao, G. (Chem. Commun., 2013)

(untitled) - Wang, H.-Y.; Zhang, K.; Zheng, C.-W.; Chai, Z.; Cao, D.-D.; Zhang, J.-X.; Zhao, G. (Angew. Chem., 2015)
Angew. Chem. ,Int. Ed. 2015, 54, 1775–1779. doi:10.1002/anie.201409342

(untitled) - Mitsunobu, O.; Yamada, Y. (Bull. Chem. Soc. Jpn., 1967)

(untitled) - Zhong, F.; Dou, X.; Han, X.; Yao, W.; Zhu, Q.; Meng, Y.; Lu, Y. (Angew. Chem., 2013)
Angew. Chem. ,Int. Ed. 2013, 52, 943–947. doi:10.1002/anie.201208285 The racemic version of this reaction was reported by this group.

Organofluorine Chemistry: Principles and Commercial Applications - Banks, R. E.; Smart, B. E.; Tatlow, J. C. (Plenum Press, 1994)